(untitled) (Journal of Applied Membrane Science & Technology, 2022)
This article presents various gas separation membrane simulation techniques based on typical engineering and design techniques for membrane process description. Modelling and design processes are tasks that use different tools to simulate the profile of the process. Given some initial data, such as flow, temperature, concentration and pressure, the correlations presented can be used to perform simulations. After selecting the flow configuration, types of membrane element and settings, it can be determined whether the process is working as expected. The design process, on the other hand, involves the specific results to be obtained, namely the material and geometry estimation of the membrane itself. This paper presents the challenges faced in the membrane simulation study for gas separation, which is important to predict and design the industry scale of gas separation process. At the same time, attainment of accurate results at non-ideal conditions remains challenging. More experimental data and research are needed to support and validate the results.